HUMANIZATION OF THE PEDAGOGICAL PROCESS AS LEADING CONDITION OF THE SPIRITUAL EDUCATION OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2022)
In this article author examines one of the most effective pedagogical conditions of spiritual senior pupils' education - humanization o f pedagogical process.